Early Indian Architecture : Cities and City Gates etc. - Coomaraswamy, Ananda K., (Brill | Manohar Publishers & Distributors, 2024)
Indian architecture is diverse and rich in its nature. This volume by Coomaraswamy centres around Buddhist architecture in ancient India. Buddhist architecture was one of the remarkable features, which gave rise to the sacred architecture in India, as it developed during the Mauryan Empire, and subsequently went to other parts of East, Central, and South East Asia. This volume discusses the importance of city and city gates from the perspective of Buddhist architecture. The work is divided into two parts: Part I deals with cities and city gates, etc. while Part II is on the Bodhi-gharas, i.e. representations of the Bodhi tree with or without a temple structure. The book looks at the Pali literature, which includes tales from Jatakas depicted in stupas located at Bharhut, Sanchi, and Amravati. These three sites are known for their ancient Indian stupa architecture around the world, which gave rise to the traditional Buddhist stupa architecture. The author also cites references from medieval architecture, such as forts, situated in Gujarat, Madhya Pradesh, Karnataka, and other parts to describe city architecture in ancient India.